2007
DOI: 10.1677/joe-07-0230
|View full text |Cite|
|
Sign up to set email alerts
|

Endoplasmic reticulum stress is involved in myocardial apoptosis of streptozocin-induced diabetic rats

Abstract: Apoptosis plays a critical role in the diabetic cardiomyopathy, and endoplasmic reticulum stress (ERS) is one of the intrinsic apoptosis pathways. Previous studies have shown that the endoplasmic reticulum becomes swollen and dilated in diabetic myocardium, and ERS is involved in heart failure and diabetic kidney. This study is aimed to demonstrate whether ERS is induced in myocardium of streptozotocin (STZ)-induced diabetic rats. We established a type 1 diabetic rat model, used echocardiographic evaluation, h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
27
0

Year Published

2010
2010
2020
2020

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 54 publications
(29 citation statements)
references
References 46 publications
2
27
0
Order By: Relevance
“…On the other hand, cells can up-regulate the expression of GRP78 to decrease the dissociation and activation. It has been reported that the expression of GRP78 increases in ers-induced apoptosis (17,20). In the present study, we also observed the expression of GRP78 increased (Fig.…”
Section: Discussionsupporting
confidence: 87%
See 1 more Smart Citation
“…On the other hand, cells can up-regulate the expression of GRP78 to decrease the dissociation and activation. It has been reported that the expression of GRP78 increases in ers-induced apoptosis (17,20). In the present study, we also observed the expression of GRP78 increased (Fig.…”
Section: Discussionsupporting
confidence: 87%
“…ers-induced apoptosis has been implicated in several diseases such as diabetes mellitus, parkinson's disease (15) and has been demonstrated in some tumor cell lines such as pc-12 neuronal cells (16) and lung carcinoma A-549 cells (17). Some drugs, ischemia-reperfusion, hypoxia and glucose starvation can disturb er function and may lead to ers (18)(19)(20). ERS initiates the unfolded protein response (UPR), which alleviates protein overload in the er (21).…”
Section: Introductionmentioning
confidence: 99%
“…It is unclear whether this effect extends to hyperglycemiainduced cardiomyocyte apoptosis. Hyperglycemia-induced cardiomyocyte apoptosis is associated with increased reactive oxygen species (ROS) production and subsequent endoplasmic reticulum (ER) stress (27,59). ER stress activates the unfolded protein response (UPR), a set of signaling pathways that halt cellular processes such as protein translation and that upregulate expression of chaperone proteins to restore normal ER function.…”
mentioning
confidence: 99%
“…Cellular metabolic abnormalities and defections of organelles were shown to participate in the pathology of DC (10)(11)(12)(13)(14), which is a chronic and complex process associated with impaired calcium homeostasis, increased lipid uptake, myocardial insulin resistance, glucotoxicity, increased oxidative stress and activation of the renin-angiotensin system (15). Furthermore, the pathological role of endoplasmic reticulum (ER) stress in DC has been noted in a number of studies (16)(17)(18).…”
Section: Introductionmentioning
confidence: 99%